The Reliability and Validity of the Measure of Criminal Attitudes and Associates and the Pride in Delinquency Scale in a Mixed Sex Sample of Justice-Involved Youth - O’Hagan, Heidi R. (Criminal justice and behavior, 2019)
It is unclear if self-report measures of criminal attitudes and associates—developed and validated predominately on adult male offender samples—can or should be used with justice-involved girls. With a sample of 300 justice-involved youth (100 females, 200 males), this study examined the reliability and validity of the Measure of Criminal Attitudes and Associates (MCAA) and the Pride in Delinquency Scale (PIDS). Both measures evidenced reliability and convergent and discriminant validity in both sexes. The MCAA and the PIDS consistently predicted general recidivism for males (majority of area under the curve [AUCs; 7 out of 10] ranged from .60 to .68), but not for females (majority of AUCs [6 out of 8] ranged from .50 to .59). Both measures predicted violent recidivism across sex, with the majority of AUCs ranging from .60 to .67. More work is needed with exclusive female samples to better understand and operationalize criminal attitudes through a gender-informed lens.